Turkey’s Accession to the European Union: Dilemma and Objections - Anastasiadou, Mersilia (Études helléniques / Hellenic Studies, 2012)
This paper will focus upon the relationship between the European Union and Turkey in its historical, institutional and political dimensions. Turkey qualifes as a sui generis state when compared to the European and Western states because of the diﬀerences in its social institutions and political culture. There is a defcit regarding democratization and rule of law. The army had until very recently a dominant role in the political system. There is an interdependence between internal political developments and the role that Turkey is projecting in international aﬀairs, which appears to inﬂuence its European future as well. The EU has laid down certain criteria which Turkey has to abide by, particularly as they relate to necessity for peaceful symbiosis, respect of international law and rules that concern Greece and Cyprus and also, the changes in the political system concerning democratization. These are the obvious conditions for the membership and fnal accession to the EU. There are also implicit fears in the European Countries, mainly in Germany and France, concerning Turkey’s size and demography and the legalization of the mass migration movement should it become part of the EU.